Safe and Compliant Guidance by a Powered Knee Exoskeleton for Robot-Assisted Rehabilitation of Gait - Beyl, P.; Knaepen, K.; Duerinck, S.; Van Damme, M.; Vanderborght, B.; Meeusen, R.; Lefeber, D. (Advanced robotics, 2011)
In the research field of robot-assisted gait rehabilitation there is increased focus on the improvement of physical human-robot interaction by means of high-performance actuator technologies and dedicated control strategies. In this context we propose a combination of lightweight, intrinsically compliant, high-torque actuators (pleated pneumatic artificial muscles) with safe and adaptable guidance along a target trajectory by means of proxy-based sliding mode control. We developed a powered knee exoskeleton (KNEXO) to evaluate these concepts. In addition to the trajectory-based controller a torque controller was implemented with a view to minimizing the interaction during unassisted walking. First, various treadmill walking experiments were performed with unimpaired subjects wearing KNEXO to evaluate the performance of the proposed controllers. Test results confirm the ability of KNEXO to display low actuator torques in unassisted mode and to provide safe, adaptable guidance in assisted mode. Subsequently, a multiple sclerosis patient participated in a series of pilot experiments. Provided there was some patient-specific controller tuning KNEXO was found to effectively support and compliantly guide the subject's knee.